Switching to a 'turn-on' fluorescent probe for rapid detection of hydrazine in human breast cancer cells using a test-strip. Issue 37 (2nd September 2022) - Karak, Anirban; Mandal, Moumi; Halder, Satyajit; Banerjee, Shilpita; Banik, Dipanjan; Maiti, Anwesha; Jana, Kuladip; Mahapatra, Ajit Kumar
Abstract : Assimilation of styryl bridge has produced a molecular probe TPSBT, capable of hydrazine detection. The appreciable enhancement in fluorescence and its low detection limit helps the probe to detect hydrazine in human breast cancer cell MDA-MB 231. Abstract : A fluorescent probe TPSBT was developed to monitor hydrazine detection with a "turn on" response, converting from a "non-responsive" probe by a simple structural modification. The probe shows very weak fluorescence due to the strong ICT process and upon treatment with hydrazine, green fluorescence appears due to the blocking of this ICT by the formation of a hydrazone. The probe TPSBT can detect hydrazine with a very low detection limit (1.22 × 10 −7 M) and within a very short time period of 50 s. Additionally, the probe is able to give a response in live cell imaging (MDA-MB 231) and also in the solid phase.